2013
DOI: 10.1371/journal.pone.0074736
|View full text |Cite
|
Sign up to set email alerts
|

Complete Sequence and Comparative Analysis of the Chloroplast Genome of Coconut Palm (Cocos nucifera)

Abstract: Coconut, a member of the palm family (Arecaceae), is one of the most economically important trees used by mankind. Despite its diverse morphology, coconut is recognized taxonomically as only a single species (Cocos nucifera L.). There are two major coconut varieties, tall and dwarf, the latter of which displays traits resulting from selection by humans. We report here the complete chloroplast (cp) genome of a dwarf coconut plant, and describe the gene content and organization, inverted repeat fluctuations, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 60 publications
11
75
0
Order By: Relevance
“…Both F. ussuriensis and F. cirrhosa chloroplast genomes had a quadripartite structure similar to most land plants consisting of a pair of IRs (52,678 and 52,156 bp, respectively) separated by LSC (81,732 and 81,390 bp) and SSC (17,114 and 17,537 bp) regions ( Figure 1, Table 1). The Fritillaria chloroplast genomes were AT-rich (63% in both species), and LSC (65.3% and 64.2% in F. ussuriensis and F. cirrhosa) and SSC (69.4% and 69.6% in F. ussuriensis and F. cirrhosa) regions were more AT-rich than the IR regions (57.6% and 57.4% in F. ussuriensis and F. cirrhosa), which is similar to other chloroplast genomes [6,7,[14][15][16].…”
Section: Chloroplast Genome Organization Of Two Fritillaria Speciessupporting
confidence: 61%
“…Both F. ussuriensis and F. cirrhosa chloroplast genomes had a quadripartite structure similar to most land plants consisting of a pair of IRs (52,678 and 52,156 bp, respectively) separated by LSC (81,732 and 81,390 bp) and SSC (17,114 and 17,537 bp) regions ( Figure 1, Table 1). The Fritillaria chloroplast genomes were AT-rich (63% in both species), and LSC (65.3% and 64.2% in F. ussuriensis and F. cirrhosa) and SSC (69.4% and 69.6% in F. ussuriensis and F. cirrhosa) regions were more AT-rich than the IR regions (57.6% and 57.4% in F. ussuriensis and F. cirrhosa), which is similar to other chloroplast genomes [6,7,[14][15][16].…”
Section: Chloroplast Genome Organization Of Two Fritillaria Speciessupporting
confidence: 61%
“…In addition, 8 editing sites in C. scarabaeoides and C. cajan were identified, which were not predicted by PREPcp. Among all the genes analyzed, ndh gene displays the maximum number of editing sites (Supplementary Tables S6, S7), ndh genes have been reported to contain maximum number of editing sites (Corneille et al, 2000; Huang et al, 2013), since they are considered to be dispensable (Burrows et al, 1998; Shikanai et al, 1998), therefore accumulation of editing sites may have been permitted in ndh transcript due to dearth of stringent requirement of ndh function.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies, using advanced genome sequencing techniques, have improved the prospects for resolving phylogenetic homogeneity at taxonomic levels and have enhanced the current understanding of the structural and functional evolution of economically important plants and their traits [1215]. In the last decade, numerous studies have reported the results of chloroplast genome sequencing for economically and ecologically important tree species, such as Eucommia ulmoides [16], Poplus cathayana [17], Quercus spinosa [18], Acacia ligulata [19], Pinus armandii [20], Cocos nucifera [21], Citrus aurantiifolia [22], Musa acuminata [23], Norway spruce [24], etc. The elucidation of the chloroplast genomes of important tree species has facilitated to understand the evaluation of gene structure and has targeted conservation and propagation strategies [1213].…”
Section: Introductionmentioning
confidence: 99%